The phenomenon of beggary and its impact on the community of the city of Al-Amarah - Wisam Dargal (collage of education / university of Misan, 2024)
Begging is a social phenomenon that affects society's structure and is a deviation from good behavior and a departure from prevailing customs and traditions because of poverty, unemployment, homelessness, family conflicts and wars. In addition, have serious implications for the beggar, his family and society, which include different ages categories for both genders and are consider a bad habits prevailing in public societies and the study area in particular. Despite of the laws against this habit, the research found that the largest number of beggar's family ranged from 5 to 12 individuals. They do not live in an owned house and adolescent teenagers, parentless and unmarried. Therefore, the phenomenon of begging deserves scientific study of its importance and it has negative repercussions on society.